Optimal. Leaf size=24 \[ -5-e^x-\frac {-3+e^{e^x}}{-1+x}+x+\log (x) \]
________________________________________________________________________________________
Rubi [F] time = 0.71, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {1-4 x-x^2+x^3+e^x \left (-x+2 x^2-x^3\right )+e^{e^x} \left (x+e^x \left (x-x^2\right )\right )}{x-2 x^2+x^3} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {1-4 x-x^2+x^3+e^x \left (-x+2 x^2-x^3\right )+e^{e^x} \left (x+e^x \left (x-x^2\right )\right )}{x \left (1-2 x+x^2\right )} \, dx\\ &=\int \frac {1-4 x-x^2+x^3+e^x \left (-x+2 x^2-x^3\right )+e^{e^x} \left (x+e^x \left (x-x^2\right )\right )}{(-1+x)^2 x} \, dx\\ &=\int \left (-\frac {4}{(-1+x)^2}+\frac {e^{e^x}}{(-1+x)^2}+\frac {1}{(-1+x)^2 x}-\frac {x}{(-1+x)^2}+\frac {x^2}{(-1+x)^2}-\frac {e^x \left (-1+e^{e^x}+x\right )}{-1+x}\right ) \, dx\\ &=-\frac {4}{1-x}+\int \frac {e^{e^x}}{(-1+x)^2} \, dx+\int \frac {1}{(-1+x)^2 x} \, dx-\int \frac {x}{(-1+x)^2} \, dx+\int \frac {x^2}{(-1+x)^2} \, dx-\int \frac {e^x \left (-1+e^{e^x}+x\right )}{-1+x} \, dx\\ &=-\frac {4}{1-x}-\int \left (\frac {1}{(-1+x)^2}+\frac {1}{-1+x}\right ) \, dx+\int \left (1+\frac {1}{(-1+x)^2}+\frac {2}{-1+x}\right ) \, dx-\int \left (e^x+\frac {e^{e^x+x}}{-1+x}\right ) \, dx+\int \left (\frac {1}{1-x}+\frac {1}{(-1+x)^2}+\frac {1}{x}\right ) \, dx+\int \frac {e^{e^x}}{(-1+x)^2} \, dx\\ &=-\frac {3}{1-x}+x+\log (x)-\int e^x \, dx+\int \frac {e^{e^x}}{(-1+x)^2} \, dx-\int \frac {e^{e^x+x}}{-1+x} \, dx\\ &=-e^x-\frac {3}{1-x}+x+\log (x)+\int \frac {e^{e^x}}{(-1+x)^2} \, dx-\int \frac {e^{e^x+x}}{-1+x} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.16, size = 35, normalized size = 1.46 \begin {gather*} \frac {3-e^{e^x}-e^x (-1+x)-x+x^2+(-1+x) \log (x)}{-1+x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.55, size = 32, normalized size = 1.33 \begin {gather*} \frac {x^{2} - {\left (x - 1\right )} e^{x} + {\left (x - 1\right )} \log \relax (x) - x - e^{\left (e^{x}\right )} + 3}{x - 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.28, size = 58, normalized size = 2.42 \begin {gather*} \frac {x^{2} e^{x} + x e^{x} \log \relax (x) - x e^{\left (2 \, x\right )} - x e^{x} - e^{x} \log \relax (x) + e^{\left (2 \, x\right )} - e^{\left (x + e^{x}\right )} + 3 \, e^{x}}{x e^{x} - e^{x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.07, size = 26, normalized size = 1.08
method | result | size |
risch | \(x +\frac {3}{x -1}+\ln \relax (x )-{\mathrm e}^{x}-\frac {{\mathrm e}^{{\mathrm e}^{x}}}{x -1}\) | \(26\) |
norman | \(\frac {x^{2}-{\mathrm e}^{x} x -{\mathrm e}^{{\mathrm e}^{x}}+2+{\mathrm e}^{x}}{x -1}+\ln \relax (x )\) | \(27\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} x + \frac {e E_{2}\left (-x + 1\right )}{x - 1} - \frac {{\left (x^{2} - 2 \, x\right )} e^{x} + {\left (x - 1\right )} e^{\left (e^{x}\right )}}{x^{2} - 2 \, x + 1} + \frac {3}{x - 1} + 2 \, \int \frac {e^{x}}{x^{3} - 3 \, x^{2} + 3 \, x - 1}\,{d x} + \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.96, size = 20, normalized size = 0.83 \begin {gather*} x-{\mathrm {e}}^x+\ln \relax (x)-\frac {{\mathrm {e}}^{{\mathrm {e}}^x}-3}{x-1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.21, size = 20, normalized size = 0.83 \begin {gather*} x - e^{x} + \log {\relax (x )} - \frac {e^{e^{x}}}{x - 1} + \frac {3}{x - 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________